Interference of apple seedling growth by green foxtail - Omezine, Abdessatar, author; Wallner, Stephen J., advisor; Zimdahl, Robert L., committee member; Rogoyski, Matthew, committee member (Colorado State University. Libraries, 1984)
Because of the documented benefits of cover crops in orchards, the interactions of one potential candidate-green foxtail (Setaria viridis L . Beauv.)-with apple seedlings (Malus domestica L.) have been investigated. Two possible interference mechanisms have been studied under greenhouse conditions: competition and allelopathic effects of green foxtail on apple seedling growth. Inhibition of apple seedling growth by green foxtail was recorded only in interference experiments where competition for water or nutrients was a present factor. No inhibition was detected when competition was removed or minimized in a hydroponic system. The incorporation of green foxtail root debris into soil mixture did not result in inhibition of apple growth. Thus, competition for water was the most likely reason for inhibition of apple seedling growth by green foxtail. The presence of green foxtail did not affect dry matter distribution in apple seedlings when water and nutrients were equally available to both plants. Studies of allometric parameters anatomical indices suggested that green foxtail roots did not release any allelopathic chemicals. Green foxtail might be used as cover crop in apple orchards when competition for water and nutrients is minimized. Elimination of competition is a difficult and expensive task and is often impossible in the field. However, the reduction of competition can be made by using strip herbicidal treatment in the tree rows.
Covers not scanned.
Keywords: Foxtail; Apples -- Diseases and pests; Cover crops; Growth (Plants)